Topiramate and accommodation: Does topiramate cause accommodative dysfunction? - ÇERMAN, EREN; ERASLAN, MUHSİN; KAHRAMAN KOYTAK, PINAR; AKKAYA TURHAN, SEMRA; TANRIDAĞ, TÜLİN (CANADIAN OPHTHAL SOC, 2017)
Objective: To investigate the accommodation function in topiramate users. Design:Case-control clinical study. Participants:The participants included 16 controls and 22 patients using 100 mg/kg topiramate who were diagnosed with migraine according to the International Classification of Headache Disorders, second edition criteria. Methods:One-minute dynamic measurements of refraction with accommodation stimuli of 0 D, 2 D, 2.5 D, 3 D, 4 D, and 5 D were obtained using the open field refractometer WAM-5500 in. Results:In most of the accommodation stimuli ranges (0 D, 2.5 D, 3 D, and 5 D), topiramate users had a significantly higher accommodative lag compared with controls (p=0.028, p =0.014, p=0.011, and p=0.011, respectively). The most important causes of accommodative lag were found to be accommodation stimulus and inclusion in the topiramate group (p<0.001, R-2=0.32, 95% CI 0.22-0.37 and 0.42-0.91, respectively). Multivariate linear regression analysis revealed that the 2 most important predictors of accommodative lag were accommodation stimulus and age (p<0.001, r=0.51, 95% CI 0.31-0.32 and 0.67-0.69, respectively) CONCLUSIONS: Even after adjustment for age, accommodative lag is greater across several accommodative stimulus levels in patients using topiramate, which may be related to visual symptoms in topiramate users.
Keywords: ANGLE-CLOSURE GLAUCOMA; DYNAMIC ACCOMMODATION; VISUAL DISCOMFORT; MYOPIC SHIFT; AGE; AUTOREFRACTOR; WAM-5500; LAG